Harmonizing Algorithms and User Satisfaction: Evaluating The Impact of Spotify's Discover Weekly on Customer Loyalty - Natasha Janice; Nurrani Kusumawati (Integrasi Sains Media, 2024)
Integrating artificial intelligence (AI) in music streaming platforms has significantly transformed user experiences, with personalized features playing a key role. This study investigates the impact of Spotify's